Sândi vocálico externo no Poruguês Arcaico - Cangemi, Ana Carolina Freitas Gentil Almeida [UNESP] (2014)
This thesis aims to study the processes of external phonological vocalic sandhi in 13th century Archaic Portuguese (AP). These processes are diphthongization, V1 elision, crasis and deletion or nonproduction of V2 and will be analyzed in 200 Cantigas de Santa Maria (CSM) from the point of view of the Nonlinear Phonology theories. The CSM are a collection of 420 chants in praise to Virgin Mary compiled in Galician- Portuguese by Alfonso X (1211-1284). We started from the scansion of the CSM verses, verifying the location of stresses and clarifying doubts about the word's delimitation in AP. The methodology aims to abstract the limits between words by from the scansion of the verses in poetic syllables and from the metrification patterns present in the CSM. The rhythmic and phonotactic contexts of application of the processes of external phonological vocalic sandhi constitute the core of our study, which extends itself to the analysis of hiatus occurrences. In the first phase of Portuguese language the results achieved reveal that the phonological processes which undo the hiatus structure nowadays started to act already in AP. Besides, those processes were expressive in AP, for instance: the elision has an application margin close to the vowels maintenance when compared to hiatus (the permanence of two vowels which are involved in word junctioncontext). Both elision and hiatus were more productive at that moment of the language than diphthongization, crasis and deletion or nonproduction of V2, which were marginal phonological processes, with more restricted application contexts. These facts are due to rhythmic, prosodic and phonotactic restrictions in AP. This thesis also studies the restructuring of the syllabic margins and of the nucleus, with emphasis to ...